Aspects of the biology of the infaunal bivalve Mollusc Solen cylindraceus (Hanley) in the Kariega estuary - De Villiers, Casper Johannes (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1990)
Solen cylindraceus is an infaunal filter-feeding bivalve inhabiting the intertidal mud banks of many southern African estuaries. It is particularly abundant in the Kariega estuary (33Â°41'S; 26Â°42'E) where it reaches densities of 400mâ »Â² (192g shell-free dry wt. mâ »Â²). The Kariega is a permanently open, marine dominated estuary about 18km in length, and S. cylindraceus is most abundant in its middle and upper reaches. Some physical characteristics of the estuary (temperature, salinity, sediment and water turbidity) are described, and the possible role of these factors in determining the density and distribution of S. cylindraceus within the Kariega estuary, is discussed. The structure of the alimentary system, gills and labial palps of S. cylintfraceus is described, all of which showed no major variation from the "typical" eulamellibranchiate form. Solen cylintfraceus was found to be a euryhaline osmoconformer with a salinity tolerance range of 15-65%. When animals were removed from their burrows, osmotic equilibration of the haemolymph was rapid (1-2 hours). By contrast, in animals left undisturbed in their burrows, osmotic equilibration was retarded (72-204 hours). It is suggested that the observed decrease in the rate of change of haemolymph osmolarity for animals in their burrows is linked to the stability of the interstitial salinity. A temperature tolerance range of 5-44Â°C was determined for S. cylintfraceus (in situ), in which prolonged exposure to 5Â°C and 40-45Â°C (12-36 hours respectively) resulted in a decreased burrowing ability, coma and death. Animal burrowing responses were not affected by temperatures in the range 15-35Â°C. Field experiments were carried out over several tidal cycles, in which the measurement of crystalline style volume was used as a means of assessing extracellular digestive activity. No major variation in style volume was recorded and it appeared that S. cylindraceus did not exhibit any cyclical pattern of style dissolution and regeneration. It is suggested that S. cylindraceus feeds continuously from the water column during high tide and possibly within its burrow, at or below the water table, during low tide. At a suspensoid concentration of 5Omg lâ »Â¹, S. cylindraceus was found to filter water almost continuously (90-95% of the time). Time spent filtering dropped to 68% at 100mg lâ »Â¹ and 32% at 500mg lâ »Â¹. Filtration rates for summer collected animals (25Â°C) were 22.86 Â± 4.36ml min.â »Â¹, some 3ml min.â »Â¹ greater than that recorded for winter (16Â°C) collected animals. Filtration rate may be expressed as a function of shell length by the equations: y=0.247xÂ¹Ì‡â °â ¶â ¶ (winter) and y=0.758xâ °Ì‡â ¸Â²â ¶ (summer). Solen cylindraceus was capable of acclimating its filtration rate to both high and low temperatures under laboratory conditions. Filtration rate exhibited a thermal optimum in the range 15-35Â°C, declining at higher and lower temperatures. Qâ‚ â‚€ values of filtration decreased rapidly from greater than 4 to less than 2, when the thermal optimum was reached. Maximum rates generally occurred at approximately 5Â°C above the temperature to which the animal had been acclimated. Optimal filtration rates (19-23ml min.â »Â¹) were recorded in the salinity range 15-45%. When subjected to abrupt changes in salinity, filtration rates were immediately depressed. The extent and duration of these decreased filtration rates were dependent upon the magnitude and direction of salinity change, and were always less in animals exposed to hyper- than hyposaline conditions. Animals exposed to increased temperature and simultaneous elevated or unchanged salinity, showed a slight increase in filtration rate followed by rapid acclimation. A decrease in both temperature and salinity resulted in an initial decrease in filtration rate and a longer acclimation period. The ability of S. cylindraceus to acclimate fully within a wide temperature and salinity range, and to filter maximally in hypersaline conditions may, in part, explain its unusually high abundance in the Kariega estuary, despite it being close to the southernmost limit of the animal's geographical distribution. No significant difference in flItration rate was recorded at suspensoid concentrations of 5-100mg 1â »Â¹. However, at 250 and 500mg lâ »Â¹ filtration rates decreased significantly, and coincided with increased levels of pseudofaecal production. Solen cylindraceus retained particles down to 2.5-3.0Âµm with great efficiency (ca. 60-90% efficiency). Below this particle size, retention efficiency decreased rapidly and a net production of particles was recorded below 1.51Âµm. Particle retention was independent of temperature (15 and 25Â°C) and salinity (15 and 35%). Use was made of stable carbon isotope analyses (Â¹Â³C/Â¹Â²C ratios) in an attempt to determine the important food sources of S. cylindraceus within the Kariega estuary. The results obtained demonstrated an enrichment in Î´Â¹Â³ values for S. cylindraceus from the upper (-27.9%) to the middle (-25%c) and lower (-21.6%o ) reaches of the estuary, with no seasonal variation apparent. The bivalve was substantially more depleted in Â¹Â³C relative to the dominant aquatic macrophytes Zostera capensis (-9.1 to -15.6%o) and Spartina maritima (-12.5%o). The use of Î´Â¹Â³ alone, however, to unequivocally "pin point" specific food sources of a filter feeder in a predominantly detritus based food web, is limited. It is suggested that in the Kariega estuary, riparian litter and other terrestrially derived vegetation contribute to the carbon pool. A possible contribution of Â¹Â³C depleted food sources via chemoautotrophic and/or anaerobic pathways, to the diet of S. cylindraceus, is suggested.
Keywords: Mollusks -- South Africa -- Eastern Cape; Bivalves -- South Africa -- Eastern Cape